Physician associates and anaesthetic associates in UK: rapid systematic review of recent UK based research - Greenhalgh, T; McKee, M (British Medical Journal Publishing Group, 2025)
Objective: To summarise research on the efficacy and safety of UK physician associates and anaesthetic associates in the context of an ongoing policy review. Design: Rapid systematic review. Search strategy: Keyword and author search of three databases; citation tracking; search of previous systematic reviews. Eligible studies: Empirical research (any design) on physician associates/anaesthetic associates in UK healthcare published between 2015 and January 2025. Main outcomes: Any measure of clinical efficacy or safety. Methods: Eligible papers were grouped into categories and appraised using Critical Appraisal Skills Programme checklists. Two reviewers independently extracted data on study designs, samples, methods, and findings. Each paper was scored for trustworthiness, generalisability, and relevance; differences were resolved by discussion. Studies meeting a minimum inclusion standard were described and critiqued. Results: Of approximately 5000 titles, 52 papers were eligible (48 on physician associates, four on anaesthetic associates), of which 29 met the inclusion standard. The total number of physician associates studied was very small, especially in primary care; no studies reported direct assessment of anaesthetic associates. Only one study, of four physician associates, involved any assessment by a doctor of their clinical competence by direct observation. No studies examined safety incidents. Some studies suggested that physician associates could support the work of ward based teams and work in emergency departments when appropriately deployed and supervised in low risk clinical settings, but the number of individuals and settings studied was small, and those findings should be considered preliminary. Physician associates seemed to struggle in primary care, however, because the role was more autonomous, the case mix was more diverse, decisions were more uncertain, institutional support was more limited, and supervision arrangements were more challenging. Staff expressed concern about physician associates’ and anaesthetic associates’ competence to manage undifferentiated, clinically complex, or high dependency patients; order ionising radiation; or prescribe. Physician associates reported a range of experiences and desired a clear role within the team. No evidence was found that physician associates add value in primary care or that anaesthetic associates add value in anaesthetics; some evidence suggested that they do not. Conclusions: The UK literature on physician associates and anaesthetic associates is sparse and of variable quality, and some is outdated. In this context, the absence of evidence of safety incidents should not be misinterpreted as evidence that deployment of physician associates and anaesthetic associates is safe. Findings of apparent non-inferiority in non-randomised studies may obscure important unmeasured differences in quality of care. New research is urgently needed to explore staff concerns, examine safety incidents, and inform a national scope of practice for these relatively new and contested staff roles. The findings from this UK based study should be interpreted in the context of the wider international evidence base. Study registration: INPLASY202520039.